GAMBARAN KOMPETENSI TENAGA ADMINISTRASI INSTALASI REKAM MEDIS DI RUMAH SAKIT UMUM DAERAH DR. ADNAAN WD PAYAKUMBUH TAHUN 2022 - SINTHA FERONIKA; ERPIDAWATI ERPIDAWATI; SYLVI NEZI AZWITA (JURNAL ILMIAH KOHESI, 2022)
Some officers work alone in carrying out work and the level of education is not in accordance with the field of work. This study aims to determine the description of the competence of medical record administration personnel at the Regional General Hospital Dr. Adnaan WD Payakumbuh. This type of research is quantitative research. Data collection in this study with a questionnaire. The sample size was 25 respondents. Data analysis techniques in this study are univariate analysis. The results of the study of 25 respondents stated that the intellectual competence of 4 (16%) respondents in the less competent category and 21 (84%) respondents in the competent category, physical competence of 5 (20%) respondents in the less competent category and 20 (80%) respondents in the competent category, personal competence of 3 (12%) respondents in the less competent category and 22 (88%) respondents in the competent category, social competence of 9 (36%) respondents in the less competent category and 16 (64%) respondents in the competent category, and spiritual competence of 8 (32%) respondents in the less competent category and 17 (68%) respondents in the competent category.